Crushed recycled glass as a filter medium and comparison with silica sand - SOYER, ELİF; AKGİRAY, ÖMER (WILEY, 2010)
The objective of this work was to evaluate crushed recycled glass as a medium for rapid filtration In the first part of this work physical and hydraulic characteristics of the glass medium were studied In the second part pilot scale mime filtration experiments were carried out using raw waters from three different water sources Two physically identical filter columns were operated in parallel in all the experiments One filter contained a silica sand medium tint is widely used in Turkey whereas the other filter contained crushed recycled glass Experiments were repeated five times as follows (i) Without the use of a coagulant (ii-iii) with 5 mg/L and 10 mg/L of alum and (iv-v) with 5 mg/L and 10 mg/L of ferric chloride Turbidity particle counts and head losses were measured and compared as functions of time The following were observed (1) Provided that a coagulant was used the filter containing crushed glass produced effluent turbidities and particle counts similar to those obtained with the sand filter (2) The crushed glass medium generated both a smaller clean bed head loss and smaller clogging head losses than those of the sand filter It is concluded that crushed glass shows significant promise as an alternative to silica sand in rapid filtration
Keywords: Crushed Glass; Filter Media; Head Loss; Particle Removal; Rapid Filtration; FILTRATION; PREDICTION; EXPANSION; DESIGN